ENTOMOPATHOGENIC FUNGI AS MYCO-BIOCONTROL AGENT OF STORED GRAIN INSECT PESTS - Adegbola, R. Q.; Adegbola, A. J.; Sanni, L.O. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
Chemical insecticides have been a fairly successful means of controlling pests that cause harm to stored agricultural commodities. However, there are risks, involved in applying these pesticides continuously; these risks are fast becoming problem of global proportion. The overuse and misuse of chemical pesticides by agricultural value chain actors has made the development of new and lower-risk, benign methods for managing insect pests necessary. One lower risk method of managing insect pest that is gaining traction in terms of utilization is myco-biocontrol, one of which is entomopathogenic fungi (EPF) with a biological origin. Entomopathogenic fungi are pathogenic to insects, and based on their widespread presence in natural environments are purported as less harmful to the environment. Toxicologically, EPF are considered benign to man, making them desirable in the context of the new integrated pest management (IPM) framework. Fundamentally, this review covers the current state of knowledge regarding EPF fungi and their use for biological pest management as well as recent developments in the bio-control of stored-grain insects using formulated and unformulated strains. It also covers the mode of application, mechanism of action, and environmental factors necessary for the germination and growth of conidia.